Design of a tsunami barrier to The North of Penang Island - Jahromi, Bahman Esfandiar (2009)
On December 26, 2004 a major earthquake with a magnitude between 9.1 and 9.3 on the Richter scale occurred off the West Coast of Sumatra, Indonesia. This earthquake generated a devastating tsunami. Several countries suffered from the gigantic tsunami, many people died and many more lost their properties. The tsunami struck the West Coast of Peninsular Malaysia and killed 68 people and destroyed many properties. The Island of Penang was one of the places that suffered from the disaster. Fifty seven people died in this area when most of them were enjoying their time on the beach. Many home appliances, several boats and fishing equipments were also destroyed in the area. In order to prevent similar damages from a possible recurring tsunami event, the Steady-State Spectral Wave (STWAVE) model of Surface Water Modelling System (SMS) has been used to design an offshore barrier to dissipate the tsunami wave energy in this study. The December 2004 tsunami was used as a reference case. Nearshore tsunami wave amplitude was obtained from field surveying data conducted on July 9-10, 2005. Whilst, offshore tsunami wave height and direction have been acquired from an output of TUNAMI-N2 program. The model which has been calibrated against field survey data showed good agreement. Several breakwater layouts were simulated in the STWAVE model to derive an optimal configuration which could dissipate the tsunami wave energy before it reaches the Penang Island shoreline. From analysis made, it was found that eleven layouts reduced the tsunami wave heights by more than 70%. After extensive evaluation, breakwater layout number 39 was selected as the optimized layout showing an efficiency at 83%. At this efficiency, a wave height of 1.02 meter would impact the shoreline should a 6.0 m tsunami wave was made to propagate from offshore.